Visual reflexive attention as a useful measure of development - Lundwall, Rebecca A. (Frontiers in Psychology, 2023)
Cognitive psychology began over three-quarters of a century ago and we have learned a great deal in that time, including concerning the development of cognitive abilities such as perception, attention, and memory, all of which develop across infancy and childhood. Attention is one aspect of cognition that is vital to success in a variety of life activities and, arguably, the foundation of memory, learning, problem solving, decision making, and other cognitive activities. The cognitive abilities of later childhood and adulthood generally appear to depend on the reflexes, abilities, and skills of infancy. Research in developmental cognitive science can help us understand adult cognition and know when to intervene when cognitive function is at risk. This area of research can be challenging because, even in typical development, the course of cognitive development for a particular child does not always improve monotonically. In addition, the typical trajectory of this development has been understood differently from different historical perspectives. Neither the history of thought that has led to our current understanding of attention (including its various types) nor the importance of developmental aspects of attention are frequently covered in training early career researchers, especially those whose primary area of research in not attention. My goal is to provide a review that will be useful especially to those new to research in the subfield of attention. Sustained attention in adults and children has been well-studied, but a review of the history of thought on the development of reflexive attention with a focus on infancy is overdue. Therefore, I draw primarily on historical and modern literature and clarify confusing terminology as it has been used over time. I conclude with examples of how cognitive development research can contribute to scientific and applied progress.